EFFECTIVE USE OF LABOR RESOURCES BY ECONOMIC ENTITIES (Eureka Journal of Computing Science & Digital Innovation, 2026)
This article analyzes the theoretical and practical aspects of the effective use of labor resources in the activities of economic entities. Factors of labor organization, employee motivation, employment growth, and labor market development are highlighted.
Keywords: Labor resources, business entities, efficiency, motivation, employment, small business.